A UV-visible-NIR active smart photocatalytic system based on NaYbF4:Tm3+ upconverting particles and Ag3PO4/H2O2 for photocatalytic processes under light on/light off conditions - Serge-Correales, York E. [UNESP]; Ullah, Sajjad; Ferreira-Neto, Elias P. [UNESP]; Rojas-Mantilla, Hernan D. [UNESP]; Hazra, Chanchal [UNESP]; Ribeiro, Sidney J. L. [UNESP] (Royal Soc Chemistry, 2021)
The development of broad-spectrum photocatalytic materials that allow the use of a larger portion (UV to NIR) of the solar spectrum for photocatalytic processes has attracted great attention. Among visible light-active photocatalysts, silver phosphate (Ag3PO4) stands out prominent for its high photocatalytic activity towards the degradation of different pollutants. However, the full potential of this photocatalyst is limited by its inherent low photostability arising from self-photoreduction and its inability to efficiently use light beyond the UV-Vis range of the solar spectrum. To address these fundamental limitations of Ag3PO4, we have developed a smart photocatalytic system by combining the interesting upconversion property of NaYbF4:Tm3+ upconverting particles (UCPs) with the exceptionally high photocatalytic activity of Ag3PO4 and the oxidizing capacity of H2O2. In this UCPs/photocatalyst/oxidant (NaYbF4:Tm3+/Ag3PO4/H2O2) system, the NIR-to-UV/visible UCPs can convert low energy NIR photons into high energy UV-visible photons that can be absorbed by Ag3PO4, thus photo-exciting (activating) it indirectly under NIR illumination. Similarly, the oxidant (H2O2) prevents self-reduction and/or assists in regeneration of Ag3PO4 through a Fenton-like process, thus ensuring the photostability and recyclability of Ag3PO4. Interestingly, the Ag3PO4/H2O2 system remains active generating reactive oxygen species even after the photoexcitation process is turned off (dark conditions). The proposed broad spectrum photocatalytic system (UCPs/Ag3PO4/H2O2) was found to exhibit a high photocatalytic response (98% degradation of crystal violet dye in 90 min) under NIR illumination from a 980 nm laser and still a higher response (100% removal in less than 8 min) under direct visible light from low-cost blue emitting LEDs.